Енергосистеми комплексного використання низькосортного твердого палива - Poljakov V.N. (General Energy Institute of the National Academy of Sciences of Ukraine, 2000)
One of ways of expansion of fuel and energy and chemical-technological base of Ukraine is complex use low quality coal in power systems, grouped on a basis of gas generators "Koppers-Totzek", "Lurgi" and "Winkler". Such power systems represent highly profitable technological systems working on a principle without ashes and with minimum influence on environment.